CO2 flux emissions from Atlantic Rainforest soil: determining the most suitable sampling time - Vitória, Edney Leandro da; Simon, Carla da Penha; Gontijo, Ivoney; Freitas, Ismael Lourenço de Jesus; Rocha Junior, Paulo Roberto (Ciência e Natura, 2020)
Few studies have established protocols for measuring CO2 emissions in the soil. In order to determine the time of day which best represents the average daily CO2 emissions, the present study evaluated the variations in CO2 emissions throughout the day and the relationship between these emissions and the soil moisture and temperature, in an attempt to standardize data collection in tropical soils. The study was carried out in an Atlantic forest fragment of the coastal tablelands, Brazil. A close relationship between CO2 emission and soil temperature was observed, with CO2 emissions decreasing as daytime temperatures increased. The soil moisture had no direct relation with the CO2 emission, but was only related to the soil temperature. Two groups of CO2 emissions were observed, forming between the sampling time from 09:00 a.m. to 10:00 p.m., and from 11:00 p.m. to 08:00 a.m. Due to the small difference found between the mean group formed between 09:00 a.m. and 10:00 p.m., which was ~ 8% when compared to the general average, and also the fact that CO2 is easier to collect during this time, it is suggested that this period is the most suitable time to collect CO2 in the field.